From bench to bedside: a call to expand physician pathways for PhDs - Ghebre, Yohannes T. (Frontiers in Education, 2025)
There are about 200 accredited medical schools in the United States. Among these, about 160 are allopathic (MD) and nearly 40 schools are osteopathic (DO). Collectively, these schools graduate over 28,000 physicians each year. In addition, over 75% of the MD schools have MD/PhD programs that train physician-scientists. Despite these relentless efforts to prepare physicians to become scientists who comprehensively understand the molecular basis of diseases and facilitate drug discovery and development efforts, there remains a notable shortage of physician-scientists. Although training established PhD-level scientists to become physicians is an attractive strategy to mitigate the shortage, there doesn't appear to be a well-defined path that trains PhDs to earn their medical degree. This problem is even more daunting for PhDs who trained outside the United States or Canada. This review highlights the advantages of training established biomedical scientists to become physicians and makes a case for medical schools to launch PhD-to-MD or PhD-to-DO programs to equip these scientists with clinical acumen to help bridge the widening gap between basic science research and clinical care as well as to mitigate our heavy and unsustainable reliance on international medical graduates to supply our medical workforce.